(untitled) (Journal of Organizational Psychology, 2022)
Studies have demonstrated the effectiveness of servant leadership on human capital and social enterprise are few. To increase knowledge, research with the Network of Youth Organizations (ROJ) in Chad was carried out. The hybrid approach has been deployed. The results showed that the credibility and human warmth of the servant leader promote the adherence and commitment of employees in the process of social entrepreneurship. Then, the passion for the excellence of the servant leaders is a real lever for the performance of social entrepreneurship. However, the passion for excellence contributes little to social entrepreneurship. But it is above all agile, autonomous and committed human capital that increases performance in social entrepreneurship. The article is useful for scholars who will find a renewed definition of servant leadership. While public actors will find new avenues of solutions to suggest policies and programs to strengthen the capacity of the OR. OR leaders will find strategies to effectively enhance and enhance their human capital.